SPECIES DIVERSITY OF THE MORACEAE FAMILY AT THE SORAYA RESEARCH STATION IN THE LEUSER ECOSYSTEM AREA, SULTAN DAULAT DISTRICT, SUBULUSSALAM CITY, ACEH PROVINCE - Hidayat, Muslich; Rizky Ahadi; Masitah (Indonesian Journal of Environmental Sustainability, 2024)
Biodiversity is defined as the number of species inhabiting a particular area. Forests serve as ecosystems dominated by diverse plant species, primarily trees, which constitute the majority of the vegetation in these landscapes. Trees play a pivotal role in shaping forest communities and function as critical life-support systems. However, frequent environmental challenges and deforestation have resulted in insufficient attention toward research on the Moraceae family. Therefore, this study aims to identify species within the Moraceae family and analyze their diversity in the Soraya Research Station area. This research was conducted in September 2023 at the Soraya Research Station, located within the Leuser Ecosystem Area, Sultan Daulat District, Subulussalam City. The study employed an exploratory method using transect sampling across three main transects, each extending 1 km. Vegetation data were analyzed using the Importance Value Index (IVI) and Shannon-Wiener Diversity Index (H'). The findings revealed the presence of 8 Moraceae species, with a total of 221 individuals belonging to 2 genera. The species with the highest IVI was Damli (Artocarpus sp), with a value of 83.54, while the species with the lowest IVI was Damli lebar daun (Artocarpus sp), with a value of 8.87. The diversity index (H') of the Moraceae family at the Soraya Research Station was classified as moderate, with an H' value of 1.575.